Individual Behavior and Group Membership - Charness, Gary; Rigotti, Luca; Rustichini, Aldo (The American economic review, 2007)
People who are members of a group and identify with it behave differently from people who perceive themselves as isolated individuals. This paper shows that group membership affects preferences over outcomes, and saliency of the group affects the perception of the environment. We manipulate the saliency of group membership by letting a player's own group watch as a passive audience as decisions are made, and/or by making part of the payoff common for members of the group. In contrast to the minimal-group paradigm, minimal groups alone do not affect behavior in our strategic environments. However, salient group membership significantly increases the aggressive stance of the hosts (people who have their group members in the audience), and tends to reduce that of the guests.